PEMODELAN METODE FUZZY INFERENCE SYSTEM (FIS) SUGENO : Untuk Penentuan Jurusan SMA Pada Siswa SMP (Studi Kasus: SMP Bakti 17 Jakarta) - Lidya Nur Prastika (2020)
Basically every human being has a different potential ability. In school education, each student's differences should be considered because it can determine the poor student's learning achievement. The school plays an important role to develop the potential of self-owned students in order to continue expanding through to the final education level. In furthering higher education the course selection for high school students is quite difficult and students feel confused in choosing the right course. To address the problem, a modeling system can be decided based on the value of the report, Psychotest value, and attitude value. Therefore, the author wanted to create a modeling system that determines the majors in high school using multiple assessment factors on students during junior high school using the Fuzzy Inference System (FIS) with the Sugeno method. This research is done so that students who will continue their education at high school level can choose the course according to the course they are assigned.